P056 The acceptability of different HIV testing options among young men living in vancouver, canada: a qualitative study. (14th July 2019) - Mniszak, Caroline; Carson, Anna; Prangnell, Amy; Shoveller, Jean; Knight, Rod
Abstract : Background: In British Columbia (BC), three testing options are available: nominal, non-nominal and anonymous. Little is known, however, about the factors that influence the acceptability of the different testing strategies, particularly among young men, a group with disproportionately low HIV testing rates. Methods: We draw on data from in-depth, semi-structured interviews with 45 young men (18–30) in Vancouver, BC, in order to identify the factors that influence the acceptability of different HIV testing options. Results: Most participants described not being aware that there were options other than nominal testing available in Vancouver. Upon learning about non-nominal and anonymous testing options, participants described seeing the value of non-nominal testing, insofar as it safeguards their privacy while at the same time providing a pathway to HIV-related health care for those who test positive. Many were concerned, however, that anonymous testing would present challenges to treatment and care for those who test positive. Others expressed concerns about the implications for public health not having access to accurate and up-to-date information about the 'state' of the HIV epidemic. Nevertheless, while participants did not tend to describe anonymous testing as something they would opt for in the future, almost all of the participants felt offering anonymous testing as an option is an important strategy to reduce barriers for key groups of young men (e.g., those living in rural communities). Conclusion: Based on our results, offering non-nominal and anonymous HIV testing represents an important step in increasing the accessibility of HIV testing for some groups of young men who found these approaches both acceptable and preferable (e.g., over nominal testing). However, within our sample, participants were not aware that anonymous and non-nominal testing were available. Developing clear and easy-to-understand communication strategies about the different approaches to testing may enhance opportunities for uptake of these approaches. Disclosure: No significant relationships.